The implementation of reading corner and teacher modeling in Indonesian learning through psycholinguistic approach - Khoiriyatun Ni'mah (Institut Agama Islam Negeri (IAIN) Salatiga, 2018)
Reading Corner and teacher modeling are strategies to improve students' learning process through habit of utilizing classroom corner as a place to read with a teacher as direct model in the activity. The purposes of this research are: 1) implementing innovative learning activities with non monotonous classroom atmosphere; 2) creating interactive and interesting learning process; 3) enhancing students' reading motivation, and; 4) improving students' academic achievement. This research is a qualitative descriptive research used to describe and analyze phenomenon and real condition in the field through psycholinguistic approach to support language learning process in order to improve students' motivation to read, write, listen and talk, which has implication to create a good teaching learning process, curriculum which is appropriate with the changes of human dimension, appropriate lesson plan, materials and syllabus for students, as well as performing appropriate assessment. Research findings showed that: 1) students have high motivation and awareness to read; 2) creating conducive learning atmosphere for students to learn; 3) the way students learn is open not solely rely on transfer of knowledge from teachers; 4) the emergence of interest in asking and discussing the information obtained from reading; 5) the emergence of students' courage in conveying the idea of the results of understanding from learning; 6) the knowledge is developed; 7) students' vocabulary mastery is getting better; 8) increasing the academic ability of students.